2008
DOI: 10.1111/j.1365-2567.2007.02740.x
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine protease cathepsin X modulates immune response via activation of β2 integrins

Abstract: Summary Cathepsin X is a lysosomal, cysteine dependent carboxypeptidase. Its expression is restricted to cells of the immune system, suggesting a function related to the processes of inflammatory and immune responses. It has been shown to stimulate macrophage antigen‐1 (Mac‐1) receptor‐dependent adhesion and phagocytosis via interaction with integrin β2 subunit. Here its potential role in regulating lymphocyte proliferation via Mac‐1 and the other β2 integrin receptor, lymphocyte function‐associated antigen‐1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 35 publications
4
37
0
Order By: Relevance
“…These motility-associated morphological changes also depend on the LFA-1 affinity and the LFA-1-cytoskeleton association [37]. Additionally, we showed that cathepsin X promotes proliferation of T cells [38]. This is consistent with the study of Wang et al demonstrating that LFA-1 affinity regulation is crucial for the activation and proliferation of naïve T cells [39].…”
Section: Discussionsupporting
confidence: 81%
“…These motility-associated morphological changes also depend on the LFA-1 affinity and the LFA-1-cytoskeleton association [37]. Additionally, we showed that cathepsin X promotes proliferation of T cells [38]. This is consistent with the study of Wang et al demonstrating that LFA-1 affinity regulation is crucial for the activation and proliferation of naïve T cells [39].…”
Section: Discussionsupporting
confidence: 81%
“…8,44 The role of CPs in AAA pathophysiology extends beyond degradation of structural extracellular matrix; these enzymes also contribute to a number of processes through other substrates such as cytokines, integrins, and other proteases. [45][46][47] We recently suggested a mechanism of microvessel growth stimulation by CatS by generating highly proangiogenic laminin-5 ␥2 fragments. 29 Consistent with this finding, we detected increased levels of such laminin-5 ␥2 fragments, colocalization of these proteins with extensive microvascularization, and strong correlation between these two variables (r 2 ϭ 0.8653, P Ͻ 0.001) in AAA lesions of CystC Ϫ/Ϫ ApoE Ϫ/Ϫ mice ( Figure 5, A-D), supporting a role for CPs in angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Initial reports have indicated that it can also act as a peptidyl-dipeptidase (9, 58) ; these indications were, however, not confirmed in later studies (59,60) . It is highly expressed in the immune system where it has been shown to regulate cell behavior and differentiation (61,62) . The cathepsin X propeptide contains an integrin-binding RGD sequence and its association with cell surface integrins has been shown to regulate cell adhesion (63) .…”
Section: Cathepsin Xmentioning
confidence: 99%